Recentering Action in Critical Consciousness - Diemer, Matthew A.; Pinedo, Andres; Bañales, Josefina; Mathews, Channing J.; Frisby, Michael B.; Harris, Elise M.; McAlister, Sara (Child development perspectives, 2021)
Scholarship on critical consciousness frames how people who are more marginalized deeply analyze, feel empowered to change, and take collective action to redress perceived inequities. These three dimensions correspond to critical reflection, motivation, and action, respectively. In this article, we aim to recenter action in scholarship on critical consciousness, given the disproportionate attention that has been paid to reflection. To achieve this aim, we review empirical associations between critical action and positive developmental consequences among more marginalized youth, highlight promising practices to foster critical action, and identify questions and key areas for inquiry. We hope this article motivates a recentering of critical action in scholarship, policy, and practice on critical consciousness.